Timing of egg laying, moult, and annual changes in body weight in captive kororā (little penguins; Eudyptula minor) at the National Aquarium in Napier, New Zealand from 2013 to 2021 : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Zoology at Massey University, Palmerston North - Ganesh, Ritika Malaika (Massey University, 2024)
This study looked at the timing of egg laying, moult, and annual changes in body weight for captive little penguins housed at the National Aquarium, Napier. The aquarium has been keeping handwritten diaries they call “penguin diaries” for each year, and these diaries hold day-to-day information about the captive little penguins. Using the data from these diaries from 2013 to 2021, we could extract dates for when eggs were laid, who laid the egg, how many were laid, the occurrence of replacement clutches and the incubation period for the eggs. In the same way, we got information about when they started and ended their moult, which allowed us to calculate the duration of the moult. The aquarium provided the monthly body weights and daily feed intake data as an Excel file. Body weight was observed with the bird's annual cycle. The timing of egg laying for the first clutch started in September, and the replacement clutch was observed in October for the second clutch and November for the third clutch. The timing of moult was observed from December to January and ranges from October to March for both male and female little penguins. An increase in body weight was seen as the bird starts to moult and would decrease as the bird undergoes their moult and would be the lowest when they come out of their moult. Feed intake would increase in December with the bird's moult coming up. Female birds showed more variation in their body weight during the breeding season than males. Therefore, the birds showed annual changes to their body weight as they progressed through their annual cycle. Their egg-laying and moult timing are similar to that of wild little penguins.
Keywords: 310903 Animal developmental and reproductive biology